A comparative study on the powers of the Sultan and the Yang Dipertua Negeri in dismissing the Menteri Besar and chief minister respectively / Mohamad Azlan Zulkifly, Ahmad Zaki Shah Shah Headan and Muhammad Asmirul Asraf Fadli - Zulkifly, Mohamad Azlan; Shah Headan, Ahmad Zaki Shah; Fadli, Muhammad Asmirul Asraf (Faculty of Law, 2011)
This study examines about the constitutional crisis which happen in Perak and Sarawak through cases of Dato ' Sen Nizar Jamaluddin v Dato' Seri Zarnbry and Stephen Kalong Ningkan v Penghulu Tawi Sli where the power of Sultan and Yang Dipertua Negeri were question in appointing and dismissing Menteri Besar and Chief Minister. By examining these cases, it reveals the standards that have been put forward out by court in sending their judgement. Plus, it explains the application of article in the state constitution. The core of the problem lies when there is no provision in state constitution that stated that Sultan and Yang Dipertua Negeri can dismiss Menteri Besar and Chief Minister. Inferences were made that there is loophole in State Constitution regarding this matter. This paper project concentrates on the determining factors that are taken into consideration by the judges in their judgement is concluded. Furthermore, this project paper also provides some recommendations and suggestions that can be considered in order to curb the problem. Therefore, it comes to the conclusion that every state constitution needs to be reviewed regarding the appointment and dismissing of Menteri Besar and Chief Minister so that it would not cause more crisis in state and to deal with the critiques made over the years.